#TITLE_ALTERNATIVE# - DANI FAUZI (NIM 10104023), UMAR
nloading process of the gas lift is a transient process in which the amount of gas is injected into the well. Then the gas pass through the surface choke to lift killing fluid coming out from the well. This thesis discusses about the elapsed time problem in the unloading process of gas lift. The problem will be devided into two parts: the first phase of unloading process and the second phase of unloading process. During the first phase of unloading process, when pure liquid exists in the tubing, the iteration depends only on time dimension. The pressure gradient equation and the height gradient of killing fluid equation in the first phase are solved numerically by the finite difference methods. During the second phase of unloading process, when two phase gas-liquid flow occurs in the tubing, the iteration depends on space and time dimension. The gradient of space in the second phase is discretized with backward Euler difference and the gradient of time in the second fase is discretized with Central Space Backward Time (CSBT) difference. In order to find the downstream pressure in the second phase, the Hagedown & Brown corellation is used and solved numerically by 4th order Runge-Kutta method. The results of the simulation with the data from the reference are given in the form of elapsed time of the unloading process of the gas lift. The elapsed time of unloading process which is based on the result of simulation is in agreement with the result of Tang. It is shown that the amount of injection gas, the amount of valve, the height of valve, and surface area of tubing and casing significantly effect the elapsed time.